Career and Basic Salary of Teachers in the Education System of the City of São Paulo - Márcia Aparecida Jacomini; Ana Paula Santiago do Nascimento; Leandro Thomazini (Universidade Federal do Rio Grande do Sul, 2018)
This article aims to analyze the dynamics of the basic teacher's salary in the education system of the city of Sao Paulo from 1996 through 2016, in relation to the National Minimum Wage, the Necessary Minimum Wage by DIEESE (SMN) and national Professional Starting Salary (PSPN). It is a documental and bibliographical research focusing on national and municipal legislation and on the analysis of the initial and final teachers' base salary. It was found that although the basic salary of municipal teachers was 40 percent higher than the PSPN in 2009, in 2016 it was only 11 percent higher. The Starting Salary was also below the SMN-DIEESE in November 2016, R$ 3,550.00 and R$ 3,940.41, respectively.